El origen céltico del topónimo Valladolid. Vallis-tolitum > Valladolid y Vallis-tolitanus > vallisoletano (Nuevos argumentos y planteamiento de la cuestión) (Minerva, 2019)
The origin of the toponymous Valladolid has been traditionally traced from an Arab occupation site, Valle de Olid. For some it comes from Vallis de Olivetum, or “Valley of the Olive Trees”.There is no evidence of the proposition “de” between Vallis > Valley and Olid, neither of anyone so called Olid and less a person of such name related with the history of our city. This made us think in an Latin-Celtic étimo as the origin of the toponymous Valladolid: therefore Vallis-tol-itum , with the meaning of “Valley of Springs, place of swamps”. Our thesis is based in: A) The diverse variants of the notarial documents dating from the XI and XII centuries to which our Valladolid resembles. B) The topographical evidence of the valley where Valladolid stands, famous to this day for its current floods due to the Pisuerga and Esgueva rivers. C) The lingustical evidence which offers us several examples of toponymous with the Celtic root Tol, that means “place of water sources, spings or swamps” in Celtic Europe and particularly Northern Spain (Toledo-ancient Toletum, Tojos, Tollo, Toja, Villa Tolit, Villoldo, Villatuelda, extra). D) As well as a numbe of words coming from the Northern Spanish romances that also trace their origin from the Celtic Tol (tojo, tollo, toldo, atolladero, toll, etc.). All of these words refer to “places of waters, springs, swamps and pools”. E) The most ancient forms of Valladolid are Valtolid, Valatoliti and other analogous variations which keep the common Celtic root Tolitum.